Regional Trade and Logistics Infrastructure: A Spatial Approach - Luisa Alamá Sabater; Laura Marquez Ramos; Celestino Suarez Burguet (European Regional Science Association (ERSA), 2011)
This paper aims to analyze whether the existing logistics platforms network in Spain affects Spanish transport demand by using a spatial framework. In particular, we use demand for transport to export goods to other Spanish provinces as a proxy for logistics infrastructure demand in Spain. Then, we obtain data for trade flows between provinces (NUTS3) in the year 2007. We also obtain data about the number and area of logistics platforms existing in each Spanish province to proxy for the transportation network structure in Spain. In a first step, we construct weight matrixes considering first-order contiguity and we obtain that spatial dependence is significant in a spatial econometric model of commodity flows (LeSage and Polasek, 2008). Secondly, we incorporate logistics network structure dependence into the model so that the spatial lags measure the impact and significance on trade flows from all origins to all destinations by considering the importance of logistics performance in the neighboring provinces. Finally, we perform the analysis for different economic activities. The results obtained provide evidence about the role of the location of logistics platforms for satisfying existing demand for transport structure in the Spanish provinces..
Keywords: 330